MANAJEMEN ASET DAERAH DI BADAN KEUANGAN DAN ASET DAERAH KABUPATEN GORONTALO - Siskawati P Moha; Arifin Tahir; Fenti Prihatini Tui (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to identify and describe (1) Regional Asset Management in the Regional Finance and Asset Agency (BKAD) of Gorontalo Regency. (2) The determining factor in Regional Asset Management in the Regional Finance Agency and Regional Assets of Gorontalo Regency. The approach used is qualitative with descriptive research type. The results of this study indicate that (1) Regional Asset Management at the Gorontalo Regency Regional Financial and Asset Management Agency (BKAD) has been running well in accordance with applicable regulations, from the beginning of the planning process, usage to the monitoring stage. It's just that for supervision carried out by inventorying assets, mistakes often occur so that they can affect the value of assets in agencies. (2) The determining factor in Regional Asset Management in the Gorontalo Regency Regional Finance and Asset Management in this case is human resources (HR), regulations and leadership commitment have been implemented properly. It's just that to improve the quality of human resources (HR) in terms of knowledge about asset management is low due to the lack of offline training activities.